Transition metal nanohybrid as efficient and stable counter electrode for heterostructure quantum dot sensitized solar cells: A trial. (1st May 2020) - Kusuma, J.; Akash, S.; Geetha Balakrishna, R.
Graphical abstract: Highlights: Heterostructure in-situ sensitization of quantum dots. Metal sulphide nano-hybrids as counter electrode. Hall effect measurements to determine electron mobility. Enhanced PCE over reported literatures. Abstract: Counter electrodes are critical components of third generation solar cells. A simple strategy of utilizing isostructural analogue of graphene, namely 2D molybdenum di-sulphide as nanohybrid with CuS as counter electrode is explored in this work. Formation of heterostructure photoanode with CdSe/CdS quantum dots along with nano-hybrid counter electrode has significantly boosted current density and open circuit voltage. The designed heterostructure and the counter electrode performs exceptionally well with good stability due to synergistic effect, thus spiking new hopes in achieving high efficiency in quantum dot solar cells.